A two way fully coupled fluid structure simulation of human ureter peristalsis. Issue 14 (26th October 2018) - Takaddus, Ahmed Tasnub; Chandy, Abhilash J.
Abstract: Numerical simulations of ureter peristalsis have been carried out in the past to understand both the flow field and ureter wall mechanics. The main objective of the current investigations is to have a better understanding of the urine transport due to the peristalsis in the ureter, thus making the information helpful for a better treatment and diagnosis of ureteral complications like urine reflux. In the current study, a numerical simulation is performed using a finite-element-based solver with a two-way fully coupled fluid structure interaction approach between the ureter wall and urine. For the first time, the ureter wall is modeled as an anisotropic hyper-elastic material based on experiments performed in previous literature on the human ureter. Peristalsis in the ureter is modeled as a series of isolated boluses. By observing the flow field it is clear that the peristalsis mechanism has a natural tendency to create a backflow as the isolated bolus moves forward. As a result, the urine can flow back from the bladder to the ureter at the ureterovesical (ureter-bladder) junctions, if the one-way valve starts to malfunction.